O Sistema de Objectivos Financeiros como Metodologia e Instrumento de Mudança Organizacional na Gestão da PME - Lucena, José Filipe Medeiros de (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2006)
In a global economy, where the importance of the PMEs is clear; as motor of the economic activity consisting by a diverse reality, fitting of the Financial Theory in the context of the PMEs is justified, in the scope of the problematic one of the financial goals system. With the text of this research, we not only intend systemize and to develop relative a theoretical body to the problematic one of the financial goals system, but also to analyser inside of the context of the industry of Tanneries, the main clarifying attributes of the respective models. Using as technique the model of Curchill and Mullins, we show as the sustainable growth can be seen of a dynamic form, detaching its potentialities through the manipulation of the growth instruments, and understands the nature and operational analysis of the financial goals and strategic consequences, with the model of Donaldson.